The Political and Economic Vision of Pope Francis: Implications for Philippine Church Mission - Imbong, Jerry D. (International bulletin of mission research, 2021)
Pope Francis, whose concern for the poor has earned him the nickname the “slum pope” in Latin America, has made it clear that no society can succeed that marginalizes the poor. Drawing on the concrete conditions of Philippine society, the pope suggests that mission should not be detached from the pastoral programs that seek to address the structural causes of poverty and inequality. Pope Francis’s political and economic vision resonates with the Philippine church’s program of “new evangelization,” which seeks sustainable and integral development and a radical change in lifestyles, modes of production, and consumption.